A comparison of race performance characteristics between elite male 50-m and 100-m freestyle swimmers based on their results - Durovic, M.; Vranesic-Hadzimehmedovic, D.; Paunovic, M.; Madic, D.; Okicic, T. (Facta Universitatis: Series Physical Education and Sport, 2019)
The aim of this research was to determine the differences in specific race performance characteristics of male swimmers in the 50-m and 100-m freestyle at the Serbia Open Championship 2017 (long-course). The overall sample included in this study consisted of 40 swimmers divided by a K-Means Cluster Analysis into three groups in relation to the results in the 50-m freestyle (G1_50, T50=23.53±.27 s, n=6; G2_50, T50=24.54±.33 s, n=18; G3_50, T50=25.52±.33 s, n=16), and 55 swimmers also divided into three groups in relation to the results in the 100-m freestyle (G1_100, T100=50.99±.82s, n=10; G2_100, T100=53.41±.48 s, n=17; G3_100, T100=56.13±1.32 s, n=28). The research results indicate that there is a difference in the specific race performance characteristics in relation to the achieved results in the 50-m freestyle, including: t10_50 (F=16.79, p=.000), SL2_50 (F=4.44, p=.019) and SI2_50 (F=13.49, p=.000), also in the 100-m freestyle, including: t10_100 (F=36.45, p=.000), SL1_100 (F=5.77, p=.005), SL2_100 (F=17.47, p=.000), SL3_100 (F=7.72, p=.001), SL4_100 (F=9.84, p=.000), SI1_100 (F=5.12, p=.009), SI2_100 (F=45.97, p=.000), SI3_100 (F=13.86, p=.000), SI4_100 (F=31.23, p=.000), SR1_100 (F=4.12, p=.022) and SR2_100 (F=6.37, p=.003). Based on these results we can draw the conclusion that swimmers who have better control over their race performance characteristics during all the segments of the race, including stroke length, stroke index and stroke rate have the potential of being faster in the 50-m and 100-m freestyle.